5′‐Adenosine monophosphate‐activated protein kinase: A potential target for disease prevention by curcumin - Soltani, Arash; Salmaninejad, Arash; Jalili‐Nik, Mohammad; Soleimani, Anvar; Javid, Hossein; Hashemy, Seyed Isaac; Sahebkar, Amirhossein (Journal of cellular physiology, 2019)
Curcumin (diferuloylmethane), a yellowish agent extracted from turmeric, is a bioactive compound known for its anti‐inflammatory, antiproliferative, antidiabetic, and anticancer activities. Multiple lines of evidence have indicated that curcumin regulates several regulatory proteins in the cellular signal transduction pathway. AMP‐activated protein kinase (AMPK) is one of the central regulators of cellular metabolism and energy homeostasis, which is activated in response to increasing cellular adenosine monophosphate/adenosine triphosphate ratio. AMPK plays a critical role in regulating growth and reprogramming metabolism and is linked to several cellular processes including apoptosis and inflammation. Recently, it has been demonstrated that AMPK is a new molecular target affected by curcumin and its derivatives. In this review, we discuss recent findings on the targeting of AMPK signaling by curcumin and the resulting impact on the pathogenesis of proinflammatory diseases. We also highlight the therapeutic value of targeting AMPK by curcumin in the prevention and treatment of proinflammatory diseases, including cancers, atherosclerosis, and diabetes. In this review, we discuss recent findings on the targeting of AMP‐activated protein kinase (AMPK) signaling by curcumin and the resulting impact on the pathogenesis of proinflammatory diseases. We also highlight the therapeutic value of targeting AMPK by curcumin in the prevention and treatment of proinflammatory diseases including cancers, atherosclerosis, and diabetes.